2022-RA-823-ESGO FOXL2 mutation detection in circulating tumor DNA of adult granulosa cell tumors as a potential biomarker for disease monitoring from the randomized ALIENOR trial, a GINECO study. (20th October 2022) - Treilleux, Isabelle; Lainé, Alexandra; Combaret, Valérie; Dalban, Cécile; Gladieff, Laurence; Chevalier, Hortense; Provansal, Magali; Kurtz, Jean-Emmanuel; Brocard, Fabien; Selle, Frédéric; Heudel, Pierre Etienne; Pautier, Patricia; et al.
Abstract : Introduction/Background: Adult granulosa cell tumors (aGCT) are rare ovarian malignant tumors harboring specific FOXL2 402C>G (C134W) mutation (96%) with multiples relapses. Serum markers are inaccurate in reflecting tumor burden, supporting the identification of new biomarkers. Methodology: Plasma samples were obtained at baseline and every 2–4 weeks for 6 months after C1D1 from patients enrolled in the ALIENOR trial (NCT01770301 ; 60 patients with relapsed sex cord-stromal tumors treated with chemotherapy +/- bevacizumab (Ray-Coquard, JAMA Oncol 2021)). Digital droplet PCR on circulating cell-free DNA was performed in 137 samples from 23 patients with FOXL2-mutated aGCT to investigate the clinical value of FOXL2 mutation on circulating tumor DNA (FOXL2mut ctDNA) for monitoring disease. Results: FOXL2mut ctDNA was detected in 10 of 23 aGCT patients' plasma (43%). The sum of the largest diameter of target lesions was 52 mm for FOXL2mut ctDNA negative and 138 mm for positive samples. No clinical factors such as age, number of relapse, metastatic sites, chemotherapy lines or surgeries were correlated to FOXL2mut ctDNA levels. Looking at individual monitoring data, a trend between clinical progression and increased FOXL2mut ctDNA levels under therapy was noted. Among 19 patients with samples at baseline and for whom subsequent blood samples were also available at progression or end of study, sensibility, specificity, positive and negative predictive values of FOXL2mut ctDNA were 70%, 89%, 87% and 72% respectively. Only one of 4 patients without FOXL2mut ctDNA at baseline turned positive at progression. With a median follow-up of 42.6 months IC95% [36.8;48.8], 4 patients died (all in the FOXL2mut ctDNA group) ( figure 1 ). Conclusion: In this small series of aGCT, monitoring FOXL2mut ctDNA seems relevant to predict RECIST or clinical progression in relapse setting. All cancer deaths were in the FOXL2mut ctDNA group. Future studies are warranted to confirm if this biomarker can avoid repetitive CTscan for surveillance.